O sacro e o oblíquo: para uma tradução dos sonetos sacros de John Donne - Martini, Marcus De (2005)
The works of the English poet John Donne (1572-1631) have been reevaluated by the literary criticism after almost three centuries of ostracism. Disapproved by Samuel Johnson in the 18th century, Donne s poetry reached its current reputation after T.S. Eliot s The metaphysical poets. Eliot drew attention to some figurative features linking Donne s works to modern poetry, such as his ability to use wit, to establish unusual metaphorical and figurative relations. However, although Donne s wit is to be found either in his secular and his sacred poetry, this somewhat ambiguous peculiarity is largely disregarded by critics. Among Donne s religious poetry, the Holy Sonnets are certainly the most important compilation. It offers the highest aesthetical accomplishment and presents a collection of religious concepts which reflect his own time and elucidate Donne s own knowledge of his world. Although religious discussions are a very important part of Donne s works, the reappraisal of his works in the 20th century focused mainly on his amatory poetry. Thus Brazilian translations and studies have given special attention to the Songs and Sonnets, often disregarding the Holy Sonnets, a choice that reveals a tendency among critics to make a radical distinction between the religious and the lyrical poet. The present work analyses the Holy Sonnets and their Brazilian translations, focusing on style as much as on the substantial ideas implicit in these poems. Our main goal has been to show Donne s ability to use his well-known pervasive style both in his religious poetry and his lyrics and to actualize in his Holy Sonnets theological concepts and figures of his own time. Thus one of the main points to be observed here, stemming from Antoine Berman s study of Donne s French translations, is the fact that Brazilian translations have occasionally fail to consider these aspects in translation and interpretation. Based on several critical approaches (Gardner, 1966; Carey, 1990 and Berman, 1995), we offer in this work a critical analysis and a new translation of the Holy Sonnets.